2010
DOI: 10.1186/1471-2202-11-62
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4 deacetylation plays a critical role in early gene silencing during neuronal apoptosis

Abstract: BackgroundSilencing of normal gene expression occurs early in the apoptosis of neurons, well before the cell is committed to the death pathway, and has been extensively characterized in injured retinal ganglion cells. The causative mechanism of this widespread change in gene expression is unknown. We investigated whether an epigenetic change in active chromatin, specifically histone H4 deacetylation, was an underlying mechanism of gene silencing in apoptotic retinal ganglion cells (RGCs) following an acute inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(168 citation statements)
references
References 53 publications
5
159
2
Order By: Relevance
“…Blocking these latter changes results in substantial cell survival that diminishes over time and modest or no regeneration (2,3,7,9,10). Subsequent changes include down-regulation of IGF1 and phospho-Akt, increases in reactive oxygen species, the unfolded protein response and endoplasmic reticulum stress, caspase activation, histone deacetylation, gene silencing, diminished intracellular cAMP, and changes in levels of anti-and proapoptotic Bcl-like proteins (4)(5)(6)8). Although the mechanistic relationships between Zn 2+ dysregulation and these other changes remains to be investigated, the observations that Zn 2+ chelation diminishes several hallmarks of RGC death (caspase 3 activation, CHOP expression, Bcl-xL down-regulation), affords long-term survival for many RGCs, and stabilizes the high but transient neuroprotective effects of pten deletion (Fig.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking these latter changes results in substantial cell survival that diminishes over time and modest or no regeneration (2,3,7,9,10). Subsequent changes include down-regulation of IGF1 and phospho-Akt, increases in reactive oxygen species, the unfolded protein response and endoplasmic reticulum stress, caspase activation, histone deacetylation, gene silencing, diminished intracellular cAMP, and changes in levels of anti-and proapoptotic Bcl-like proteins (4)(5)(6)8). Although the mechanistic relationships between Zn 2+ dysregulation and these other changes remains to be investigated, the observations that Zn 2+ chelation diminishes several hallmarks of RGC death (caspase 3 activation, CHOP expression, Bcl-xL down-regulation), affords long-term survival for many RGCs, and stabilizes the high but transient neuroprotective effects of pten deletion (Fig.…”
Section: +mentioning
confidence: 99%
“…Under normal circumstances, retinal ganglion cells (RGCs), the projection neurons of the eye, cannot regenerate axons after the optic nerve has been damaged and soon undergo cell death, leaving victims of traumatic or ischemic nerve injury or degenerative conditions, such as glaucoma, with permanent visual losses. Optic nerve injury leads to numerous pathological changes in RGCs and reversing some of these changes improves cell survival, although these effects are often transitory and for the most part promote little or no axon regeneration (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Regeneration per se can be induced by intraocular inflammation combined with elevated cAMP (11,12), counteracting cell-intrinsic (13)(14)(15) or cellextrinsic (16,17) suppressors of axon growth, oncomodulin and other growth factors (18)(19)(20)(21)(22), or elevated physiological activity (23,24).…”
mentioning
confidence: 99%
“…For example, in the case of axon injury, incoming calciumencoded signals (17) or ERK-dependent signals (112) alter the neuronal epigenome, inducing changes in histone modifications that together regulate a proregenerative transcriptional response. In case of neurodegenerative disease or conditions of cell death following certain trauma, alteration in the epigenome may also contribute to repress gene expression (113,114). Neuronal activity, similarly to axon injury leads to HDACdependent histone modifications, coupling synaptic activity to changes in gene expression which are critical to neuronal plasticity (115).…”
Section: Figmentioning
confidence: 99%
“…ChIP analyses using an H4Ac antibody show decreasing promoter acetylation of several RGC genes including Thy1, Brn3b, Nrn1, Fem1c, and the anti-apoptotic genes BclX, corresponding to decreased transcription. Pretreatment with trichostatin A of RGCs following optic nerve crush reversed H4 deacetylation, and preserved Fem1c transcription [40]. Using similar models, others have shown that treatment with HDAC inhibitors such as valproic acid (Val), sodium butyrate and trichostatin A can promote RGC survival, neuronal outgrowth, after mechanical (crush) and ischemia/reperfusion injury of the optic nerve and retina [95][96][97][98].…”
Section: Histone Acetylation In Retinal Ganglion Cellsmentioning
confidence: 99%
“…As a result, histones, especially H4, become hypoacetylated, and normally expressed genes are silenced [40,119]. Subsequently, pro-apoptotic and stress-response genes show increased histone acetylation as they are activated.…”
Section: Histone Modifications In Photoreceptor Gene Expressionmentioning
confidence: 99%